Metacognitive In Reading: The Awareness of Less Proficient EFL Learners on Reading Strategies - Delti Yulita (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This article addresses the profiles of metacognitive reading strategies used by less proficient EFL learners in one public university in the east of Indonesia. Data were collected from 54 undergraduate students using MARSI (Metacognitive Awareness Reading Strategy Inventory) questionnaire. The questionnaires were analyzed using descriptive and inferential statistics which revealed the level of metacognitive reading strategies used by the less proficient EFL students. The analysis found that there is a high level of using Support Strategy (M=3.92, SD=1.22) and followed by Problem Solving Strategy (M=3.91, SD=1.1) and a medium level of using Global Strategy (M=3.39, SD=1.05). The finding revealed the lack of reading strategy instruction that concern the global analysis of the text. The results suggest that the less proficient EFL students need to generate their metacognitive level on global analysis strategies to improve their reading comprehension.